Collaborative relationship discovery in BIM project delivery: a social network analysis approach - Wang, Yongqi (2022)
A deeper understanding of collaboration among various stakeholders is imperative towards the success of the Building Information Modelling (BIM) enabled project delivery. A systematic research framework is proposed to properly analyze dynamic changes in stakeholders and their relationships by deploying social network analysis (SNA), assisting in stakeholder management. First, the work breakdown structure (WBS) is performed to organize a BIM project (i.e., rail project) into 4 levels: project name, stage, process, and activity. Second, different stakeholders are clarified based on the activity level over the whole project using interviews and surveys. Third, a project-level social network containing both the project ontology and stakeholders is established, from which cooperation information is then precisely extracted and stakeholder-level social networks with only stakeholders being nodes are created. Finally, SNA is carried out at both network- and node- levels. The results show that: (i) It is feasible to mine the collaboration information between different stakeholders through a project-level social network, (ii) The most active and central actor in each stage is continually changing, and the degree centrality and betweenness centrality are polarized between the stakeholders, (iii) There is a trend for a central stakeholder to be active and a broker at the same time, such as architect (#3), BIM coordinator (#4), BIM modeler (#6), civil & structural engineer (#9), and mechanical & electrical engineer (#18), and (iv) BIM coordinator (#4) should be given more attention, especially from the tender stage on. The research can contribute to both theoretical and practical development: (a) A new novel approach that could make the dynamic collaboration characteristics explicit was proposed with SNA, (b) A good knowledge of the dynamic collaboration attributes among different stakeholders in BIM-based rail projects could encourage a better project outcome.